Caracterização física e mecânica de blocos estruturais - Custódio, José Geraldo (2013)
This work has as main objective to present a study of the physical and mechanical properties of concrete and ceramic blocks for structural purposes. Initially we discuss the current scenario construction, in particular the use of structural masonry building process in Brazil. Additionally, we present laboratory tests performed with two specimens of structural blocks, a concrete brick and a clay brick, for the dimensional and visual appearance index, water absorption and resistance to compression. At the end, we made a discussion of which blocks can be used for structural purposes.